Improved catalytic combustion of methane using CuO nanobelts with predominantly (001) surfaces - Kong, Qingquan; Yin, Yichun; Xue, Bing; Jin, Yonggang; Feng, Wei; Chen, Zhi-Gang; Su, Shi; Sun, Chenghua (Beilstein Journal of Nanotechnology, 2018)
Through computational calculations, CuO(001) has been identified as an active surface for methane oxidation. Experimental validation with CuO nanobelts comprised of predominantly (001) surfaces has been performed and it is confirmed that the performance of such nanobelts is much higher than normal nanoparticles and nanowires. First principle calculations further clarified that two-coordinated oxygen plays a key role for methane adsorption and oxidation.
Keywords: catalytic oxidation; copper oxide; density functional theory; methane

(untitled) - Demoulin, O.; Navez, M.; Gaigneaux, E. M.; Ruiz, P.; Mamede, A.-S.; Granger, P.; Payen, E. (Phys. Chem. Chem. Phys., 2003)

(untitled) - Cullis, C. F.; Willatt, B. M. (J. Catal., 1983)

(untitled) - Choudhary, T. V.; Banerjee, S.; Choudhary, V. R. (Appl. Catal., A, 2002)

CRC Handbook of Chemistry and Physics - Haynes, W. M. (CRC Press, 2014)

(untitled) - Ciuparu, D.; Lyubovsky, M. R.; Altman, E.; Pfefferle, L. D.; Datye, A. (Catal. Rev.: Sci. Eng., 2002)

(untitled) - Cargnello, M.; Delgado Jaén, J. J.; Hernandez Garrido, J. C.; Bakhmutsky, K.; Montini, T.; Calvino Gámez, J. J.; Gorte, R. J.; Fornasiero, P. (Science, 2012)

(untitled) - Farrauto, R. J. (Science, 2012)

(untitled) - Chen, J.; Arandiyan, H.; Gao, X.; Li, J. (Catal. Surv. Asia, 2015)

(untitled) - Farrauto, R. J.; Hobson, M. C.; Kennelly, T.; Waterman, E. M. (Appl. Catal., A, 1992)

(untitled) - Gélin, P.; Primet, M. (Appl. Catal., B, 2002)

(untitled) - Abbasi, R.; Huang, G.; Istratescu, G. M.; Wu, L.; Hayes, R. E. (Can. J. Chem. Eng., 2015)

(untitled) - Nilsson, J.; Carlsson, P.-A.; Fouladvand, S.; Martin, N. M.; Gustafson, J.; Newton, M. A.; Lundgren, E.; Grönbeck, H.; Skoglundh, M. (ACS Catal., 2015)

(untitled) - Kozlov, S. M.; Neyman, K. M. (J. Catal., 2016)

(untitled) - Mayernick, A. D.; Janik, M. J. (J. Catal., 2011)

(untitled) - Pi, D.; Li, W. Z.; Lin, Q. Z.; Huang, Q. F.; Hu, H. Q.; Shao, C. Y. (Energy Technol., 2016)

(untitled) - Bychkov, V. Y.; Tulenin, Y. P.; Slinko, M. M.; Khudorozhkov, A. K.; Bukhtiyarov, V. I.; Sokolov, S.; Korchak, V. N. (Catal. Commun., 2016)

(untitled) - Hayes, R. E.; Kolaczkowski, S. T.; Li, P. K. C.; Awdry, S. (Chem. Eng. Sci., 2001)

(untitled) - Ahmadi, T. S.; Wang, Z. L.; Green, T. C.; Henglein, A.; El-Sayed, M. A. (Science, 1996)

(untitled) - Xie, X.; Li, Y.; Liu, Z.-Q.; Haruta, M.; Shen, W. (Nature, 2009)

(untitled) - Yang, H. G.; Sun, C. H.; Qiao, S. Z.; Zou, J.; Liu, G.; Campbell Smith, S.; Cheng, H. M.; Lu, G. Q. (Nature, 2008)

(untitled) - Su, D.; Xie, X.; Dou, S.; Wang, G. (Sci. Rep., 2014)

(untitled) - Hu, W.; Lan, J.; Guo, Y.; Cao, X.-M.; Hu, P. (ACS Catal., 2016)

(untitled) - Du, G. H.; Van Tendeloo, G. (Chem. Phys. Lett., 2004)

(untitled) - Huang, H.; Yu, Q.; Ye, Y.; Wang, P.; Zhang, L.; Gao, M.; Peng, X.; Ye, Z. (CrystEngComm, 2012)

(untitled) - Dey, K. K.; Kumar, A.; Shanker, R.; Dhawan, A.; Wan, M.; Yadav, R. R.; Srivastava, A. K. (RSC Adv., 2012)

(untitled) - Zhang, Q.; Zhang, K.; Xu, D.; Yang, G.; Huang, H.; Nie, F.; Liu, C.; Yang, S. (Prog. Mater. Sci., 2014)

(untitled) - Ercolino, G.; Grzybek, G.; Stelmachowski, P.; Specchia, S.; Kotarba, A.; Specchia, V. (Catal. Today, 2015)

(untitled) - Jin, Y.; Sun, C.; Su, S. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Kohn, W.; Sham, L. J. (Phys. Rev., 1965)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Kresse, G.; Joubert, D. (Phys. Rev. B, 1999)

(untitled) - Goerigk, L.; Grimme, S. (J. Chem. Theory Comput., 2010)

(untitled) - Henkelman, G.; Jónsson, H. (J. Chem. Phys., 1999)